Evaluation of antimicrobial and cytotoxic activity of fungi isolated from marine samples collected in Cu Lao Cham sea area, Quang Nam Province - Nguyen, Mai Anh; Le, Thi Hong Minh; Vu , Thi Quyen; Doan, Thi Mai Huong; Pham, Van Cuong; Vu, Thi Thu Huyen (Vietnam Journal of Marine Science and Technology, 2024)
Marine-derived fungi repeatedly showed potential bioactive activity against strains of pathogenic microorganisms. The objectives of this study were to isolate and identify the marine fungi strains from Cu Lao Cham, Quang Nam, and to evaluate the cytotoxic activity of the antimicrobial and cancer cells of their crude extracts. Seven media for culturing fungi were used. Forty-four independent isolates that look like fungi were successfully obtained from 15 marine samples. Each pure fungal isolate was cultivated on a PDA medium at 25oC for about two weeks and then extracted with ethyl acetate. All crude extracts of isolated fungi were tested for antimicrobial activity against seven ATCC pathogenic strains using the broth microdilution method and cytotoxic activity using three cancer cell lines: human liver cancer HepG2, human breast cancer MCF-7, and human lung cancer A549. Of forty-four fungal isolates, 32/44 strains showed antimicrobial activity against at least one ATCC pathogenic strain. Notably, 3/44 extracts (VH7, VH26, VH29) showed remarkable effects of antimicrobial activity against more than four pathogenic strains. The cytotoxicity results showed that 5/44 isolates (VH7, VH15, VH26, VH29, VH30) had potential activity with the percent growth inhibition of cells (% Inhibition ± SD) more than 50%. Three potential strains VH7, VH26, and VH29 were selected for further studies. Molecular identification showed that all three promising candidates belong to Aspergillus versicolor and their 18S rRNA gene sequences were deposited in GenBank under accession numbers PP762309 for VH7, PP767325 for VH26, and PP809383 for VH29. These potent strains are being further investigated for their ability to produce bioactive compounds.